(untitled) (Pulse, 2015)
A descriptive cross-sectional study was conducted for a period of six months in some locations of Dhaka city. Data was collected from 90 floating sex workers to find out their socio-demographic characteristics, sexual lifestyle particularly safe sex by using condom among them. Of the 90 respondents, mean age of the respondents was 22.21 (+4.87) with a range of < 18 to >26 years. 42 (46.7%) of the respondents were married. 73 (81.1%) of the respondents were the main earning member of the family. The mean family income was Taka 7700 (+3872.838). Majority 33(36.7%) of the respondents were illiterate. The main reason for accepting sex selling profession it was found that more than half i.e. 62 (68.9%) of the respondents were bluffed and 24 (26.7%) respondents accepted this profession of their own will. The duration of sex work of 29 (32.2%) of the respondents was less than 1 year (6-8 months) and 24 (26.6%) of the respondents were 4-5 years. 59 of the respondent always used condoms (65.6%). A significant number of respondents, 31 (34.4%) did not use condom. The reason for not using condom was clients dissatisfaction (25, 80.6%) and 4 (12.9%) respondents used other methods of contraception. Among the respondents, 78 (86.7%) used condom during last sexual intercourse. In the study, 45 (76.3%) respondents knew condom as a preventive measure and advocated its use in each sexual intercourse. (?² = 4.356; d f=1 P= 0.037). 60 (76.3%) of the respondents knew condom use as a preventive measure and used it in last sexual intercourse and highly significant association was found (?² = 17.61; df=1 P<0.001) between knowledge and practice. Promoting constant condom usage with clients among the female floating sex workers should be sustained and reinforced. Pulse Vol.7 January-December 2014 p.29-37